2018
DOI: 10.1109/jmems.2018.2797133
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Multiscale Model of MEMS Stiction Accounting for High-Order Statistical Moments of Non-Gaussian Contacting Surfaces

Abstract: Abstract-Stiction is a failure mode of microelectromechanical systems (MEMS) involving permanent adhesion of moving surfaces. Models of stiction typically describe the adhesion as a multiple asperity adhesive contact between random rough surfaces, and they thus require a sufficiently accurate statistical representation of the surface, which may be non-Gaussian. If the stiction is caused primarily by multiple asperity adhesive contact in only a small portion of the apparent area of the contacting surfaces, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Because the surface roughness is of random nature, the apparent force evolution at the meso-scale exhibits uncertainties. Hoang et al (2017Hoang et al ( , 2018 have generated random surfaces, standing for micro-scale realisations w k ∈ W, from which the apparent contact force evolution F M (d M ; X, w k ) could be predicted from a micromechanics model standing as high-fidelity model. Clearly the evolution is non-linear with the separation distance d M , and, in order to perform stochastic analyses of the MEMS behaviour, a stochastic low fidelity model of the adhesive contact force was developed.…”
Section: Meso-scopic Constitutive Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the surface roughness is of random nature, the apparent force evolution at the meso-scale exhibits uncertainties. Hoang et al (2017Hoang et al ( , 2018 have generated random surfaces, standing for micro-scale realisations w k ∈ W, from which the apparent contact force evolution F M (d M ; X, w k ) could be predicted from a micromechanics model standing as high-fidelity model. Clearly the evolution is non-linear with the separation distance d M , and, in order to perform stochastic analyses of the MEMS behaviour, a stochastic low fidelity model of the adhesive contact force was developed.…”
Section: Meso-scopic Constitutive Behavioursmentioning
confidence: 99%
“…The vectors q k M correspond to observations of the random vector Q M : W → 4 . Hoang et al (2017Hoang et al ( , 2018 have shown that two neighbouring SVEs ω(X; w k ) and ω(X ; w k ) yield spatially uncorrelated apparent properties Q M . Following the discussion in Section 5.1.4, the apparent properties were thus considered as random vectors and not random vector fields.…”
Section: Meso-scopic Constitutive Behavioursmentioning
confidence: 99%
“…Through the wavelet packet decomposition and reconstruction of compressor vibration signal, and the compressor fault diagnosis method under the combination of neural network, the diagnosis accuracy can reach 97% [3]. The combination of adaptive bistable random justice and multi-scale noise demodulation can effectively identify the weak vibration caused by the blade crack of centrifugal compressor [4]. The compressor fault diagnosis based on deep learning and local mean decomposition can learn the fault features adaptively, and the corresponding classification accuracy can reach 92.72% under the condition of low signal-to-noise ratio (SNR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of adhesive contact widely existing in the micro/nano-electro-mechanical system (MEMS/ NEMS) is an important factor to determine the performance and reliability of MEMS/NEMS [1,2]. It has a serious impact on the precision and stability of the system, and even directly causes irreversible damage.…”
Section: Introductionmentioning
confidence: 99%